Evaluation of Land Suitability For Durian (Durio Zibethinus) Plants In Parmaksian District, Toba Regency - Haholongan Sidabuke, Simon; Abdul, Rauf; FS, Harahap (Jurnal Online Pertanian Tropik, 2024)
Durian (Durio zibethinus) is known as a plant that has a fairly high economic value which is widely planted on community land in Parmaksian District, Lauhanbatu Regency, North Sumatra Province. This study aims to evaluate the land suitability class for durian as an agroforestry plant in Parmaksian, Toba Regency. Research activities include several stages of activities, namely: preparation, survey, soil analysis in the laboratory, data processing, and mapping. The survey method was carried out to collect soil samples in the field. Durian land suitability class was analyzed using the matching method. The method refers to the references and criteria adopted from the Soil Suitability of Agricultural Crops by the Center for Soil and Agroclimate Research, Bogor, Indonesia. The results showed that the actual land suitability class for durian plants in Parmaksian sub-district, was marginally suitable (S3) on Land Units 1 and 6 and not suitable (N) on Land Units 2, 3, 4, and 5 with limiting factors. are temperature and soil texture. The results of the GIS analysis show that 52.5% of the total sub-district area is marginally suitable (S3) and 47.8% of the total sub-district area is not suitable (N).